Visualization experiment and numerical calculation of the cavitation evolution inside the injector ball valve. (1st December 2022) - Liu, Jingbin; Liu, Zhenming; Wu, Jiechang; Li, Ziming; Chen, Ping; Gu, Xiaolei
Highlights: Visualization experiment of equal proportion of the ball valve in injector control valve. Interaction of cavitation between different parts of control valve. Development law of cavitation in control valve. Abstract: The generation and development of cavitation in the flow channel inside the injector ball valve had been characterized using a high-speed visualization system. The flow field information was obtained by numerical calculation of the dynamic boundary conditions. The generation mechanism and distribution law of cavitation in the ball valve were analyzed. The results show that cavitation first occurs at the gap of ball valve and then the diversion hole and the outflowing control-orifice (OA); the low-pressure area created by the throttling effect is the main factor in causing cavitation; and the flow line and vortex have a significant impact on cavitation distribution. The flow state of the fluid in the diversion hole and OA has a direct and obvious effect on the cavitation in the ball valve chamber. In the case of inlet pressure 35 MPa, when cavitation is stable, the vapor volume fraction of 0.7–1.0 accounts for 9% of the ball valve chamber volume, 89% of the diversion hole and 13% of the OA, and in case of 15 MPa they are <1%, 87% and 14%.